Situações de conflito no contexto escolar: propostas dialógicas em busca da construção de cultura de paz - Mofarrej, Graziella Jones Caccavale (2016)
In the complex contemporary world with its constant changes and in front of an exhaust of the traditionalist thought, we feel the need to develop new ways of thinking, understanding and acting. Hence, this thesis emphasizes conflicting situations commonly seen as a negative event, as opportunities of construction of dialogue. This work developed a qualitative/research-intervention inside post-modern paradigms, utilizing the social constructionist perspective as a theoretical referential. The study was conducted from an investigation about the way teachers from the seventh and eighth grade of middle school, would position themselves in a public school in the outskirts of Sao Paulo, towards conflicting situations caused between them and the adolescent students. Considering the adolescence as a significative phase in the process of changes and the school as an environment that enables the occurrence of conflicts and new learning, it was proposed as the main objective, to present facilitating practices of dialogue to the teachers, in order to offer better connection and understanding between them and the students, favoring the shared responsibilities between both parts towards situations of conflict. It is intended then to enable a more significant learning associated with the concepts of Culture of Peace promoting a more optimal and liberating education identified with the four pillars of education according to the Delors Report (UNESCO). It was organized five meetings, as an open group, of which seven teachers took part. The material used to sensitize was a film which talks about conflicts between one teacher and his students. All participants from the group were invited to narrate their personal experiences on conflict in their professional every-day life, identifying themselves with the main conflictive points presented in the film. Subsequently, the teachers were presented through experiences to the principles of Non Violent Communication, developed by Marshall Rosenberg, as a tool used to deal with relationships on a more careful way, as well as other experiences based on dialogical practices. All the narratives taken were analyzed, categorized and interpreted according to the theory that supports this work. Six months later a questionnaire was applied in order to evaluate the impact of this intervention. The results were analyzed according to the social poetics, revealing some remarkable moments, which characterized the construction of a new meaning in the relations between them. We can see, though, difficulties expressed by teachers concerned with essentialist postures and the influences dictated by the distorted marks of today‟s society, including the devaluation of their role. The experiment showed that continuous work would be necessary in order to implement changes, but dialogical proposals can be used to improve the relations between teachers and students towards the Culture of Peace